PENGEMBANGAN APLIKASI MOM (MORAL OF MOSLEM) UNTUK PEMBENTUKAN AKHLAK TERPUJI SISWA KELAS 6 SEKOLAH DASAR - Friska Siti Mutammimah; Dea Nur Hafifah; Putri Nur Deswanti; Salsabila Amalia; Ani Nur Aeni (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2021)
The development of technology in the era of 4.0 is very rapid and commendable moral values that have been rarely found in children today are the background for the development of the MOM application (Moral Of Moslem) as a learning medium that is expected to foster commendable morals in elementary school students in grade 6. This research aims to design and develop a MOM application that is suitable for use in accordance with the 8th lesson of Islamic Religious Education and Budi Pekerti in the 6th grade of elementary school. The method used in this study is Design and Development. This MOM application received an assessment from media experts of 90.75% as well as an assessment from material experts with an average of 93.75% with the interpretation of both being